Cholinesterases and anticholinergic medications in postoperative pediatric delirium - Meyburg, Jochen; Ritsert, Mona-Lisa; Traube, Chani; Plaschke, Konstanze; Haken, Rebecca von (Pediatric critical care medicine, 2020)
Objectives: - To describe the relationships between anticholinergic drug exposure, cholinesterase enzyme activity, inflammation, and the development of postoperative delirium in children. - Design: - Single-center prospective cohort study. - Setting: - Twenty-two bed PICU in a tertiary-care academic medical center in Germany. - Patients: - A consecutive cohort of children admitted after major elective surgery. - Interventions: - Children were screened for delirium bid over 5 consecutive postoperative days. Acetylcholinesterase and butyrylcholinesterase plasma activity levels were measured prior to surgery and once daily during the 5 day study period. Number of anticholinergic drugs and Anticholinergic Drug Scale score were calculated for each patient. - Measurements and Main Results: - Ninety-three children (age range, 0-17 yr) were included. The number of anticholinergic drugs as well as the Anticholinergic Drug Scale score were significantly correlated with development of postoperative delirium, independently of disease severity. Baseline cholinesterase enzyme levels did not differ between patients who did and did not develop postoperative delirium. Butyrylcholinesterase levels, but not acetylcholinesterase levels, dropped by 33% postoperatively, independent of the presence of postoperative delirium. Postoperative butyrylcholinesterase levels were inversely related to number of anticholinergic drugs, Anticholinergic Drug Scale score, and C-reactive protein levels. - Conclusions: - Anticholinergic drug exposure was related to development of postoperative delirium in this cohort, with demonstration of a dose-response relationship. As there are alternative options available for many of these medications, it may be reasonable to avoid anticholinergic exposure in the PICU whenever possible.